Imposto sobre serviços - ISS na importação e na exportação de serviços - Abreu, Anselmo Zilet (2018)
The Federal Constitution of 1988, when predicting that it is the responsibility of the complementary law to exclude from the incidence of the ISS the exports of services abroad, signaled by the adoption of the principle of destination for the tax, as it did with other taxes that affect circulation or consumption. However, unlike social and intervention contributions and ICMS, for the ISS, the CF did not foresee immunity for exports, nor did it expressly provide for the taxation of imports. The task was referred to the complementary legislator, who made the adoption of the principle with the edition of LC n. 116/2003, ruling that the tax is not levied on exports and that it is levied on the service coming from outside the country or whose service has started abroad. For the export, the norm brought an exemption, generating great controversy, because, instead of defining what exports of services are, prescribes that the services developed in Brazil are not included as exports, if the result of which is verified here. Due to the imprecision of the expression "result of service", two currents were formed: (i) which results is the execution of the service itself, in which case it would only be considered export if the service is performed outside the country; and, (ii) that result is the enjoyment of the service, so that there would be considered export even if the service was provided in Brazil, if the utility occurs abroad. The first interpretation does not give meaning to the existence of the norm, ecause the service provided outside the country would no longer be taxed, in view of the principle of territoriality. Thus, one must understand the result as fruition, occurring the export when the service is sent abroadand its usefulness is outside the country, which is the only interpretation that makes the principle of destiny effective. As far as the taxation of the importation of servicesit would have been perfectly possible if the supplementary law had provided for such cases, the fruition of service as an incidence hypothesis and the service taker as a taxpayer, which would be permitted by CF / 88. However, the law describes as an incidence hypothesis only the provision of services and as a taxpayer only the provider, having provided the service taker or the intermediary as tax substitutes. For services initiated abroad, the forecasts are valid, and it is possible to levy the tax, because the tax fact is practiced here by the taxpayer. But in the case of services from abroad, the incidence is not valid, because contrary to territoriality, LC n. 116/2003 attempts to reach a fact that occurred outside the spatial scope of the incidence hypothesis and reach a person who is not related to the tax authorities, with no valid connection element for taxation